Analysis of Achaemenian Art and Architecture with Reference to Origins, Influences, and Development. Ph. D. Vol. I - Katrаk, Verā Sohrab (1958)
M. E. L. Mallowan; Typescript; Part I: Architecture: 1. Rock-cut tombs; 2. Free standing tombs; 3. Masjid-i-Suleiman; 4. Pasargadae; 5-6. Persepolis; 7. Susa and other Achaemenian sites.